2014
DOI: 10.1007/s00109-014-1130-9
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inflammation enhances NGF-β/TrkA system expression via EGFR/MEK/ERK pathway activation in Sjögren’s syndrome

Abstract: NGF-β and TrkA expression is elevated in salivary gland epithelial cells of primary Sjögren's syndrome (pSS). Overexpression of NGF-β/TrkA system in pSS occurs via EGFR/Raf-1/MEK/ERK pathway. In pSS, NGF-β overexpression was prevented by EGFR/Raf-1/MEK/ERK pathway inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Estrogen has favorable effects on reducing pain, 18,28,29 but no certain mechanisms have been identified. From others' work, we knew that ERK was involved in the NGF upstream 42 and downstream 33 pathways. So we investigated the role of MEK-ERK in chondrocyte NGF metabolism.…”
mentioning
confidence: 99%
“…Estrogen has favorable effects on reducing pain, 18,28,29 but no certain mechanisms have been identified. From others' work, we knew that ERK was involved in the NGF upstream 42 and downstream 33 pathways. So we investigated the role of MEK-ERK in chondrocyte NGF metabolism.…”
mentioning
confidence: 99%
“…pSS glandular lymphocytic infiltrate contains T and B cells, which in association with resident epithelial cells, generate a proinflammatory microenvironment containing IL-1, IL-6, TNF-α and IFN-γ 16 , 17 among other cytokines 25 27 , a number of chemokines 18 , 19 , as well as growth factors, such as nerve growth factor-β 28 . It has been suggested that the mechanism for gland destruction in pSS is the apoptosis of ductal cells.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, on the basis of clinical observation, pSS was defined as an "autoimmune epithelitis" [12]. Indeed, SGEC are capable of releasing many cytokines that result overexpressed and thus act as key molecules in chronic inflammation, contributing to both systemic and exocrine manifestations of pSS [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. A number of explanations has been offered for the dysregulated cytokine network in pSS and, in the past, the presence of anti-Ro/SSA and anti-La/SSB antibodies was shown to be related to increased glandular and extra-glandular manifestations.…”
Section: Sjögren's Syndromementioning
confidence: 99%